The role of teachers in delivering education about respectful relationships: exploring teacher and student perspectives. Issue 4 (17th June 2014) - Ollis, Debbie
Abstract: The focus of this article is a school-based respectful relationships (RRs) pilot project involving grade 8 and 9 students. The project sought to develop a primary prevention approach to gender-based violence (GBV) in Australia. Of particular concern is the curriculum delivery component of a whole school approach that was piloted over a 10-week period in four High Schools in Melbourne, Victoria in 2010. Using data collected from teachers and students through survey, focus group interviews and student written reflections, the article identifies the key role of the teacher, the curriculum materials and the curriculum context in assisting teachers to teach about GBV. Although there was opposition to teaching specifically about GBV by some male teachers, the data indicate that this did not detract from teachers exploring these issues under a 'RRs' framework. Through 'supported risk taking', and the adoption of participatory teaching approaches and affirming and inclusive classrooms, teachers and students ended up with a positive experience of teaching and learning about GBV.